Effects of using mobile-based virtual reality on Chinese L2 students' oral proficiency. Issue 3 (12th May 2021) - Xie, Ying; Chen, Yan; Ryder, Lan Hui
Abstract: This article reports a mixed-methods study about using virtual reality (VR) tools (Google Cardboard and Expeditions) for developing students' oral proficiency in learning Chinese as a second language. Twelve students role-played as tour guides for six locations throughout a semester: four of them with VR tools and two without. Data collection included oral presentations recorded at four different times of the semester (for Presentations 1, 3, 4, and 6), class observations, participants' reflection papers, and individual interviews at the end of the semester. Results revealed that the content and vocabulary of participants' oral presentations when using VR tools scored statistically significantly higher than when not using VR tools. Qualitative data showed that participants felt that VR tools facilitated preparation and encouraged active learning.